Tiếng Hán du lịch thực dụng（实用旅游汉语） - Đỗ Mai (Đại học sư phạm Giang Tây, 2014)
This is a textbook of Chinese for foreigners with the characteristic of situational teaching. Set in traveling in Xian, it teaches oversea students how to speak Chinese in situations like finding food and accommodation, using public transportation, seeing around, shopping, contacting others by telecommunication, being in a bank and tackling with emergencies.